PENGARUH DISIPLIN KERJA DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT. SARI LEMBAH SUBUR RIAU - FIRMANSYAH, FIRMANSYAH; CHANDRA, RONI; ANDRY, ANDRY (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2023)
Employee performance is the ability of a company to manage existing resources so that it can provide value to the company, in order to know the performance of a company we can measure the level of efficiency and productivity of the company and with the performance appraisal in the company can find out how far a company has developed. The results of the research partially show that the disciplinary variable has a significant effect on the performance of employees at PT. Sari Lembah Subur, partially (t test), shows that the communication variable affects the performance of employees at PT. Sari Lembah Subur, and work discipline and communication simultaneously influence or significantly affect employee performance